A Comparative Study of Character Education Models in Japan and Indonesia: Implications for Strengthening Islamic Education - Nyimas Fakhriah; Maryamah Maryamah (Journal of Islamic Education Students (JIES), 2026)
This study aims to analyze the comparison of character education models in Japan and Indonesia and their implications for strengthening Islamic education. Character education has become a central focus in global education systems as it plays a crucial role in developing students’ moral values and social responsibility beyond cognitive intelligence. This study employed a qualitative approach with a comparative method. Data were collected through documentation studies of books, scientific journals, and relevant policy documents and analyzed using content analysis. The findings reveal that both Japan and Indonesia place moral development as an essential component of their national education systems. However, each country demonstrates distinctive characteristics and approaches shaped by their philosophical, social, and cultural foundations. The comparison indicates that the effectiveness of character education is determined not merely by the number of instructional hours but by the consistency of implementation, the strength of supportive cultural environments, and the synergy among schools, families, and communities in fostering students’ character development. These character education models also have implications for strengthening Islamic education through curricular integration and the development of moderate, tolerant, and globally minded character.